THE PEDAGOGIKAL POTENTIAL OFINTEGRATING MIFOLOGICAL CHARACTERS IN THE EDUCATIONAL PROCESS - Orazkhan, Nazerke Nurbotayevna; Askarova, Altynay Shaulievna (SCIENCE and SOCIETY, 2026)
The article analyzes the educational potential of Cossack legends and fairy tales, as well as the use of legendary heroes in the educational process. The importance of legendary prose in preserving the national worldview, historical memory, and spiritual values is emphasized. The article analyzes the possibilities of shaping the moral qualities of the younger generation, developing their national consciousness, and instilling spiritual and cultural values through historical figures and wise characters preserved in the national memory. The research findings indicate that the systematic use of legendary heroes in the educational process has a positive impact on an individual's psychological and moral development.
Keywords: folklore; legendary heroes; education; national values; spiritual heritage; historical figures; folk prose